2016
DOI: 10.1016/j.jid.2015.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Dieckol Ameliorates Atopic Dermatitis in NC/Nga Mice by Suppressing Thymic Stromal Lymphopoietin Production

Abstract: We also thank the NHLBI GO Exome Sequencing Project (see http://evs.gs.washington.edu/EVS/) and its ongoing studies that produced and provided exome variant calls for comparison: the Lung GO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
(13 reference statements)
1
9
0
Order By: Relevance
“…The in vivo antiallergic effect of the isolated dieckol was demonstrated in that percutaneous and oral dieckol administration suppressed ear swelling induced by three sensitizers in mice (Table 2), which corroborates other reports. Dieckol was reported to alleviate passive cutaneous anaphylactic reactions and atopic dermatitis in NC/Nga mice (Ahn et al, 2015;Yang et al, 2016), and supporting literature confirms the in vivo effects observed in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The in vivo antiallergic effect of the isolated dieckol was demonstrated in that percutaneous and oral dieckol administration suppressed ear swelling induced by three sensitizers in mice (Table 2), which corroborates other reports. Dieckol was reported to alleviate passive cutaneous anaphylactic reactions and atopic dermatitis in NC/Nga mice (Ahn et al, 2015;Yang et al, 2016), and supporting literature confirms the in vivo effects observed in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Bone marrow-derived primary macrophages (BMDMs) were prepared after bone marrow was isolated from C57BL/6 mice as described previously [18]. Cell culture was performed as previously described [19]. Briefly, BMDMs were cultured in Dulbecco’s modified eagle medium (DMEM) containing 10% ( v / v ) fetal bovine serum (Invitrogen, Carlsbad, CA, USA), 10,000 units/mL of penicillin, and 10,000 μg/mL of streptomycin (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the modulation of TSLP expression may be an effective strategy to prevent atopic dermatitis symptoms, balancing Th1 and Th2 immune responses. Our previous study showed that dieckol, a phlorotannin isolated from Ecklonia cava , suppressed TSLP production in mouse skin, reduced Th2-type immunity, and alleviated atopic dermatitis-like symptoms in the NC/Nga mouse model of AD ( Yang et al ., 2016b ). In this study topical application of Phloxine O, a cosmetic colorant, inhibited TSLP production and downregulated Th2 cytokines, such as IL-4, IL-5 and IL-13, resulting in decreased IgE and histamine levels.…”
Section: Discussionmentioning
confidence: 99%